Sexual Function After Intracavitary Vaginal Brachytherapy for Early-Stage Endometrial Carcinoma. Issue 4 (1st May 2012) - Quick, Allison M.; Seamon, Leigh G.; Abdel-Rasoul, Mahmoud; Salani, Ritu; Martin, Douglas
Abstract : Objective: To describe the effects of intracavitary brachytherapy (IVB) on sexual function and quality of life of women with early-stage endometrial cancer. Methods: Women with International Federation of Gynecology and Obstetrics stage I to stage II endometrial cancer treated surgically with or without IVB were identified and mailed questionnaires. Quality of life and sexual function were measured using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 and the cervical cancer disease-specific module. Pertinent data from prior surgery and radiation treatments were abstracted retrospectively. Linear transformation of the survey subscale scores was conducted per European Organization for Research and Treatment of Cancer guidelines. Results: Sixteen women in the IVB arm and 53 in the surgery-alone group completed the survey. Of the sexually active patients, 33% of the IVB patients and 42% of the surgery-alone patients felt their vagina was dry during sexual activity ( P = 0.804) and 17% versus 20% felt their vagina was short ( P = 0.884). Seventeen percent of patients in the IVB group felt their vagina was tight compared to 29% in the surgery-alone group ( P = 0.891) and 0% versus 14% of patients reported pain during intercourse ( P = 0.808). There was no statistically significant difference in sexual/vaginal functioning, sexual worry, or sexual enjoyment between the 2 groups. Conclusions: Although both groups report vaginal changes that may affect sexual function, the patients treated with IVB reported similar outcomes on a sexual function questionnaire compared to patients treated with surgery alone.